Effects of Robots on Engineering Students'Attitude - Çiftçi Özüorçun, Nilcan (Muş Alparslan Üniversitesi, 2019)
Roboticallows engineering students to understand to do analysis, design, andimplementation while working. The usage of robotic for engineering educationaims to increase student understanding with real practices. The Computerprogramming course is the main course of engineering faculty. Generally, students get difficulties to understand the logic of programming course andthey have a negative bias about that course. This study attempts to examine theeffect of the robots on students'attitude in the programming course. With thisaim, a hundred students are divided into two groups as experimental and controlgroups. Students who are in the experimental group used computer and robots andcontrol group students used a computer. Computer Programming Attitude Scale wasapplied to both groups to determine students'attitudes. The statisticalresults showed that robot usage has affected positively the experimental groupof students’ attitude in the computer programming course.

Robotik, mühendislik öğrencilerinin çalışırken analiz, tasarım ve uygulama yapmalarını sağlar. Robotik'in mühendislik eğitimi içinkullanımı, öğrencilerin gerçek uygulamalarla anlamalarını arttırmayı amaçlar.Bilgisayar programlama dersi mühendislik fakültesinin ana dersidir. Genelolarak, öğrenciler programlama dersinin mantığını anlamakta zorluk çekerler vebu ders hakkında olumsuz bir önyargıya sahiptirler. Bu çalışma, programlamadersinde robotların öğrencilerin tutumları üzerindeki etkisini incelemeyeçalışmaktadır. Bu amaç doğrultusunda yüz öğrenci deney ve kontrol grubu olmaküzere iki gruba ayrılmıştır. Deney grubundaki öğrenciler bilgisayar, robot vekontrol grubundaki öğrencileri bilgisayar kullandılar. Öğrencilerin tutumlarınıbelirlemek için her iki gruba da Bilgisayar Programlama Tutum Ölçeğiuygulanmıştır. İstatistiksel sonuçlar, robot kullanımının deney grubundakiöğrencilerin bilgisayar programlama dersindeki tutumunu olumlu yöndeetkilediğini göstermiştir.
Robotların Mühendislik Öğrencilerinin Tutumlarına Etkisi
anemon
Keywords: Computer Engineering; Engineering Education; Programming; Robotic Learning; Bilgisayar Mühendisliği; Mühendis Eğitimi; Programlama; Robotik Öğrenme